Optimizing Pregnancy for Intergenerational Health Benefits - Zachary M Ferraro (University of Ottawa Journal of Medicine, 2017)
Pregnancy is a critical period of body weight regulation for both mother and baby. Vital energy-sensing processes are established in utero that aid in nutrient storage and metabolic control later in life. Excessive weight gain during pregnancy and a surplus of maternal resources leads to preferential shuttling of nutrients and growth-promoting peptides across the placenta, resulting in fetal overgrowth — a well-established predictor of childhood obesity. Physical activity during pregnancy offers a safe and accessible way in which one can modify these intricate cellular networks across the maternal-placental-fetal interface to prevent dysregulation and optimize fetal birth weight. This commentary highlights the clinical utility of physical activity during pregnancy and provides practical recommendations as a way to ensure the best health and safety of mother, baby, and future generations.